Penerapan Strategi ‘Ada Tawa Ceria’ Dan Media Film Pendek Dalam Pembelajaran Menulis Teks Narasi Peserta Didik Kelas VII SMPN 25 Semarang 2022/2023 - Wiwin Kurnia; Eva Ardiana Indrariani; Rawinda Fitrotul Mualafina (Simpati, 2024)
This research was motivated by the writing ability of class VII participants which was still not optimal. All of this is based on the fact that interest in writing is still low, difficulty in expressing ideas or ideas into narrative texts, often looking at original texts when creating stories or essays. This research aims to describe the application of the "Ada Tawa Ceria" strategy and short film media by Elka Sinema in learning to write narrative texts for class VII students at SMPN 25 Semarang for the 2022/2023 academic year. This research uses a qualitative approach. Data collection techniques use test and non-test techniques. The test technique consists of assigning narrative text writing skills according to the short film shown by paying attention to the structure of the narrative text. Non-test techniques include observation, interviews, questionnaires and documentation. Based on the results of data analysis, it can be concluded that the "Ada Tawa Ceria" strategy and short film media can be applied to students, especially when learning Indonesian with narrative text learning material. This learning strategy and learning media can be an alternative for teachers in teaching narrative text material.